THE ROLE OF SHARIA COOPERATIVES IN SUPPORTING THE SUSTAINABLE DEVELOPMENT GOALS (SDGs) 2030 IN MEDAN CITY - Barus, Elida Elfi; Al Mujadid, Nabil Shawab; Umar, M. Ridwan; Endri Dores; Nabila Rizsyalwa Zahra (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
The implementation of the SDGs in Indonesia and Medan in particular still faces several challenges, such as poverty and inequality. Therefore, an active role from various parties, including sharia cooperatives, is needed to support the implementation of the SDGs. This article aims to analyze the role of sharia cooperatives in supporting the achievement of the 2030 Sustainable Development Goals (SDGs) in the city of Medan. The methodology of  this scientific paper uses a quantitative method with the Analytical Hierarchy Process (AHP) analysis technique. Data sources were obtained from 12 sharia cooperatives in Medan City by involving 45 respondents consisting of cooperative administrators, members, and related stakeholders through questionnaires and interviews. The results show that sharia cooperatives in Medan City have a contribution to the SDGs, especially in the goals of poverty alleviation, economic growth and decent work, and reducing inequality. The role model of sharia cooperatives in supporting the SDGs developed in this article demonstrates that the primary priority is the innovation of sharia cooperative products and services in Medan City, followed by the second priority of strengthening the capacity of sharia cooperatives. The third priority is the expansion of networks and access to cooperatives and the last priority is the partnership and collaboration of sharia cooperatives in the city of Medan. The implications of this article have a theoretical impact on the future model analysis and development of sharia cooperatives. They can also inform the practical development of innovations and services of sharia cooperatives as a strategic instrument in achieving the 2030 SDGs in the city of Medan.